The relevance of somatostatin receptors in thyroid neoplasia. - Ahlman, H. (Yale Journal of Biology and Medicine, 1997)
111In-octreotide scintigraphy in patients with persistent medullary thyroid carcinoma (MTC) visualized tumors in about half of the surgically explored sites. Tumor visualization correlated with rapid tumor growth and large tumor volume as judged from calcitonin levels. The 111In concentration ratio between tumor (T) and blood (B) in surgically excised lymph node metastases of MTC showed a large variation, with low values for microscopic and high values for macroscopic metastases in individual patients. Three cases of MTC, Hürthle cell adenoma and papillary thyroid cancer are reported with preoperative scintigraphy, T/B ratios and Northern analyses of the surgical biopsies. Visualization of tumors was possible in the absence of sstr2 (the high affinity receptor for octreotide) with the exception of microscopic tumor growth. T/B values in the patient with Hürthle cell adenoma were similar to those found in the contralateral thyroid lobe with goitre. The relatively high uptake of 111In in benign thyroid conditions probably limits the use of octreotide scintigraphy in the diagnosis of primary tumors. The technique has certain advantages over radioiodine scintigraphy after the surgical treatment of thyroid tumors: no need for withdrawal of thyroxin substitution; a possibility to diagnose metastases of tumors that do not concentrate radioiodine (MTC, Hürthle cell cancer); and complementary information about metastatic sites of non-medullary thyroid cancer (papillary and follicular tumors).